Methods of Measuring Musical Tension: Commentary on Teo (2020) - Trevor, Caitlyn (Empirical Musicology Review, 2020)
This commentary discusses the motivation, methods, and results of Teo's (2020) article on using Aggregate Voice-Leading (AVL) motion to predict perceived harmonic tension within post-tonal, neoclassical repertoire. The successes of the study as well as possible improvements are furthermore discussed. The final section contemplates some of Teo's results in light of BaileyShea and Monahan's (2018) embodied theory of analyzing and describing musical energetics such as tension. This embodied theory does not rely on tonality to operate and is therefore applicable to many genres of music. It could be an especially useful theory for analyzing genres of music for which past models of harmonic tension are insufficient, such as post-tonal or electroacoustic music.